The Importance of Moderate or Intense Low Oxygen Dilution MILD Combustion and The Impact on The Global Warming - M. M., Noor (Faculty of Mechanical & Automotive Engineering Technology, 2021)
The energy demand is dramatically increasing due to the growth of the world's population and substantial economic development mainly in Brazil, Russia, China, and India. Combustion of fossil fuel is projected to fulfil about 75 percent of this energy needs.